Current Trajectories in Global Pentecostalism: Culture, Social Engagement, and Change - Roger G. Robins (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This path-breaking collection brings together thirteen leading scholars from the humanities and social sciences to address some of the most pressing issues in contemporary global Pentecostalism. Representing institutions from eight different nations on four continents, these scholars perceptively illuminate vital matters ranging from politics, cultural performance, and sexual identity to history, theology, and socioeconomics. The articles are grounded in primary research conducted in Africa, Australia, Europe, and South America and informed by cutting-edge interdisciplinary perspectives, making "Current Trajectories in Global Pentecostalism: Culture, Social Engagement, and Change" a must-read for serious students of global Pentecostalism.